Conformity in Christ - K. Waaijman (Acta Theologica)
This essay investigates the notion of conformity in Christ as it is part of a comprehensive, multilayered process of transformation. In the first part it focuses on the process of transformation in creation, re-creation, conformity, love and glory. In the second part it discusses transformation in Christ by looking at conformation and unformation. From the viewpoint of spirituality, conformity in Christ is part of a comprehensive, multilayered process of transformation. After a short overview of this process, conformity in Christ will be discussed.